SOCIO-ECONOMIC LIFE OF FISHERMEN COMMUNITY IN TANJUNGBALAI CITY OF NORTH SUMATERA PROVINCE - Chaterine Nofelita; Kusai Kusai; Darwis Darwis (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT            The research was conducted on 19 March 2018 until 31 March 2018 which is located in Tanjungbalai city of North Sumatera Province. This research was qualitative research methods which is a research that seeks to understand and interpret the meaning of an interaction event of human behavior in certain situations according to the researcher’s own perspective.            Consumptive behavior is very clear when fishing communities are not going to sea, they spend a lot of time outdoors such as having drinks in cafes, karaoke and coffee in the shop spending money on unnecessary things around the city of Tanjungbalai. It has become a habit of behavioral patterns of fishing communitieseveryday.Keywords: fishing communities, behavioral patterns